PREFERENSI PENGGEREK BATANG PADI PUTIH Scirphopaga innotata Walker (Lepidoptera : Pyralidae) PADA TIGA VARIETAS PADI GOGO - Flora Pasaru; Shahabuddin Shahabuddin (Universitas Tadulako, 2011)
The study was conducted to evaluate eggs lay preferences of white stem borer (Scirphopagainnotata) on three varieties of dry land rice. The experiment was set up in a CompletelyRandomized design consist of three varieties (Habo, Superwin dan Sunggul Manohon) with fivereplicates. Preference test was arranged in free chosen and non chosen test. Parameter measuredwas the number of eggs oviposited by Scirphopaga innotata 4 days after application. The resultsshowed that the highest number of eggs was recorded in Superwin variety followed by Habo andSunggul Manohon. The data suggested that Habo and Superwin varieties were more preferred as ahost plant by Scirphopaga innotata compared with Sunggul Manohon and indicated that bothvarieties were more susceptible to Scirphopaga innotata.Key words: Dry land rice, preferences, rice white stem borer.